Future cathode materials for lithium rechargeable batteries - Ritchie, A; Giwa, C; Lee, J; Bowles, P; Gilmour, A; Allan, J; Rice, D; Brady, F; Tsang, S (Elsevier, 1999)
Lithium rechargeable batteries are now well established as power sources for portable equipment, such as portable telephones or computers. Future applications include electric vehicles. However before they can be used for this, or other price-sensitive applications, new cathode materials of much lower cost are needed. Possible cathode materials are reviewed.